Prophylactic Antibiotic Regimens In Tumor Surgery (PARITY): a multi-center randomized controlled study comparing alternative antibiotic regimens in patients undergoing tumor resections with endoprosthetic replacements—a statistical analysis plan - Schneider, Patricia (Trials, 2021)
BACKGROUND: Limb salvage with endoprosthetic reconstruction is the current standard practice for the surgical management of lower extremity bone tumors in skeletally mature patients and typically includes tumor resection followed by the functional limb reconstruction with modular metallic and polyethylene endoprosthetic implants. However, owing to the complexity and length of these procedures, as well as the immunocompromised nature of patients treated with chemotherapy, the risk of surgical site infection (SSI) is high. The primary research objective of the Prophylactic Antibiotic Regimens In Tumor Surgery (PARITY) trial is to assess whether a 5-day regimen of post-operative antibiotics decreases the risk of SSI at 1 year post-operatively compared to a 1-day regimen. This article describes the statistical analysis plan for the PARITY trial. METHODS/DESIGN: The PARITY trial is an ongoing multi-center, blinded parallel two-arm randomized controlled trial (RCT) of 600 participants who have been diagnosed with a primary bone tumor, a soft tissue sarcoma that has invaded the bone or oligometastatic bone disease of the femur or tibia that requires surgical resection and endoprosthetic reconstruction. This article describes the overall analysis principles, including how participants will be included in each analysis, the presentation of results, adjustments for covariates, the primary and secondary outcomes, and their respective analyses. Additionally, we will present the planned sensitivity and sub-group analyses. DISCUSSION: Our prior work has demonstrated (1) high rates of SSI after the treatment of lower extremity tumors by surgical excision and endoprosthetic reconstruction, (2) highly varied opinion and practice among orthopedic oncologists with respect to prophylactic antibiotic regimens, (3) an absence of applicable RCT evidence, (4) extensive support from international investigators to participate in a RCT, and (5) the feasibility of conducting a definitive RCT to evaluate a 5-day regimen of post-operative antibiotics in comparison with a 1-day regimen. TRIAL REGISTRATION: ClinicalTrials.gov NCT01479283. Registered on 24 November 2011